Balancing Competing Interests: Discharge by Certificate of the Official Assignee - MOHAN, S. Chandra (Institutional Knowledge at Singapore Management University, 1999)
After more than a hundred years, Singapore made major reforms to its bankruptcy laws in 1995. These changes attracted considerable public interest, with the Government taking pains to emphasise that the new law was designed to “strike a balance between the interest of the debtor, the creditor and society”. The greatest scrutiny of the provisions, to determine whether in law and in practice the competing interests of debtors and creditors could effectively be balanced, was in respect of the discharge provisions. In this article, the writer, who was then the Official Assignee, discusses how the novel remedy of discharge by certificate of the Official Assignee was conceived, drafted and successfully implemented.